Prevalence of osteoporosis and its associated factors in older adult’s users of the Primary Health Care - Daniel Vicentini de Oliveira; Gustavo Vinicius do Nascimento de Oliveira; Diogo Alves da Silva; Naelly Renata Saraiva Pivetta; Mateus Dias Antunes; José Roberto Andrade do Nascimento Júnior; Cláudia Regina Cavaglieri (Revista Brasileira de Atividade Física e Saúde)
This study examine the prevalence and factors associated to osteoporosis among older adults users of the primary health care. This cross-sectional study was carried out with 654 older adults (56% women) from primary health care in Maringá, Paraná, Brazil. The instruments used were the sociodemographic questionnaire and the International Physical Activity Questionnaire (IPAQ), short version. Data analysis was conducted through Chi-square test and Binary Logistic Regression (p < 0.05). The results showed a prevalence of 15.6% of older adults who reported the presence of osteoporosis. There was a higher prevalence of women with osteoporosis (p = 0.001), and on the other hand, there was a greater proportion of married elderly individuals (p = 0.003), and elderly with income above three minimum wages (p = 0.020) with absence of osteoporosis. The results showed that women (OR = 4.45; 95%CI: 2.47-8.01) and the older adults who take more than two medications (OR = 1.67; 95%CI: 1.15-2.42) were more likely to present osteoporosis. Older adults who presented a history of falls are 47.0% more likely to present osteoporosis. It was concluded that sex, the amount of medications and the history of falls are associated with the prevalence of osteoporosis in the older adults.